A Tactical Strategy in Transportation Problems Using Statistical Process - Sumathi, P.; V. Sathiya Bama, C. (International Journal of Engineering and Technology, 2018)
In this paper, a new algorithm is projected for finding initial basic feasible solution (IBFS) using average and also compared various methods of transportation problems. The proposed approach is also discussed with various numerical problems.Â Â